Harvestmen (Arachnida: Opiliones) in Eocene Rovno amber (Ukraine) - Mitov, Plamen G.; Perkovsky, Evgeny E.; Dunlop, Jason A. (Zootaxa, 2021)
Six species of harvestman (Arachnida: Opiliones) are documented from the Eocene Rovno amber in Ukraine. From the suborder Eupnoi we record Caddo dentipalpus (C. L. Koch & Berendt, 1854) (Caddidae), Amilenus deltshevi Dunlop & Mitov, 2009 (Phalangiidae) and Dicranopalpus ramiger (C. L. Koch & Berendt, 1854) (family incertae sedis). To these we add a new phalangiid, Metaphalangium martensi sp. n., which is the oldest representative of the Recent genus Metaphalangium Roewer, 1911 and new genus for the amber fauna. From Dyspnoi we record Sabacon claviger (Menge, 1854) (Sabaconidae) and propose Parahistricostoma gen. n. (Nemastomatidae), to accommodate Nemastoma tuberculatum C. L. Koch & Berendt, 1854, yielding Parahistricostoma tuberculatum (C. L. Koch & Berendt, 1854) comb. n. The Rovno harvestman fauna is briefly compared to both Baltic and Bitterfeld amber. The fossil species, C. dentipalpus, A. deltshevi, D. ramiger and P. tuberculatum occur in all three ambers, and S. claviger is found in Baltic and Rovno amber. The only genus and species unique to Rovno amber is thus our new taxon M. martensi. The composition of the Rovno opilionid fauna is discussed in the context of late Eocene palaeoenvironment and ecological preferences and the fossils are compared to the distribution of extant harvestman taxa. The oribatid mite Platyliodes ensigerus Sellnick, 1919 (Acari: Neoliodidae) is reported from Rovno amber for the first time.